A Rare Complication of Abdominal Drain: Fallopian Tube Herniation Through the Drain Site - Dilek Uygur; Seval Erdinç; Hülya Dede; Ümit Taşdemir; Oktay Kaymak; Nuri Danışman (Gynecology Obstetrics & Reproductive Medicine)
Prophylactic drainage of the peritoneal cavity after obstetrical and gynecological surgery is widely practiced. The idea of “when in doubt, drain” is accepted and applied clinically by many surgeons. However, surgically placed drains are not without risk. The present case describes herniation of fallopian tube during the removal of a surgical drain placed after a cesarean section.